Negotiating Tradition, Becoming American : Family, Gender, and Autonomy for Second Generation South Asians. - Salam, Rifat Anjum (New Americans (LFB Scholarly Publishing LLC), 2013)
Salam examines how second generation South Asian Americans assimilate by analyzing their family experiences, their structural circumstances and their adult life choice through the lens of arranged marriage. Arranged marriage, as an analytical frame, uncovers the ways in which gender, autonomy and intergenerational dilemmas shape individual lives. Contrary to popular assumptions about South Asians, the subjects of this study are not bound by the traditions of arranged marriage, but rather their experiences reflect a great deal of variation, negotiation, compromise and a nuanced understanding of.